Cicero ad colloquium evocatus - Albrecht, Michael von (Prometheus, 2021)
In this poetical dialogue in Latin hexameters the author portrays himself in conversation with Cicero about the greatness of the latter’s works and their influence on posterity.
Gesehen am 02.08.2023